Lean manufacturing and its application in the plastics industry - Monserrate Salvatierra, Dayanara Daily (2025)
This article comprehensively reviews the implementation and impacts of Lean Manufacturing in the plastics industry, with the aim of synthesizing and evaluating how the adoption of these methodologies has contributed to improving efficiency, reducing costs and optimizing production processes. Using a systematic review methodology, 97 relevant articles were selected. The main results of the review indicate that Lean not only improves operational efficiency and reduces waste significantly, but also encourages the integration of advanced technologies such as Industry 4.0. In addition, a strong focus on sustainability is observed, with Lean facilitating practices that support environmental conservation and carbon footprint reduction. In conclusion, while Lean Manufacturing has proven to be an effective tool for improving operations, its effective implementation requires tailored approaches that consider the cultural and structural particularities of each company.